Implementasi Metode Preview, Question, Read, Reflect, Recite & Review dalam Menghafal Hadits pada Mata Kuliah Hadits Tarbawi: Studi di Institut Agama Islam Ma'arif NU Metro Tahun Akademik 2015 - Zarnuji, Ahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2017)
Memory is an essential condition for the knowledge of Islam. Scholars of hadith and fiqh scholars in ancient times would appreciate a strong memory and memory expansion regard to memorize as one of the goals of education. Lately emerging paradigm that states that do not have to memorize so that the value of creativity can not develop the ability to think someone. But the study of hadith tarbawi, the ability to memorize is indispensable. memorizing hadith is one indicator of competency to be achieved if students want to pass on the course Hadith Tarbawi. Therefore, choosing the right method to memorize very important. One method is a method that can be applied preview, question, read, reflect, recite and review. In this paper displayed on How the process of applying methods preview, question, read, reflect, recite and review in memorizing hadith and any obstacle and support the implementation of methods methods preview, question, read, reflect, recite and review in memorizing hadith and how solutions in overcoming barriers to implementation methods preview method, question, read, reflect, recite and memorize it in review.